1998
DOI: 10.1159/000013394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Angiotensin-Converting Enzyme Inhibitors on Response to Erythropoietin Therapy in Chronic Dialysis Patients

Abstract: Background: Erythropoietin (EPO) therapy is a common and effective treatment for the correction of anemia in patients with end-stage renal disease. Simultaneous treatment with angiotensin-converting enzyme (ACE) inhibitors for the control of hypertension and/or heart failure is often necessary. Recent reports in the literature have raised concern about a potential interaction between these drugs, with a resultant decreased EPO efficacy. Methods: To investigate whether this interaction occurs in chronic dialysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
0
22
1
Order By: Relevance
“…Angiotensin II modulation of erythropoietin production is hypothesized to occur via activation of AT1 receptors and/or altered renal hemodynamics (Gossmann et al, 2001;Benohr et al, 2004). However, other studies found no causative link between erythropoietin and anemia induced with ACE inhibitors or AT1 receptor antagonists (Perazella et al, 1995;Charytan et al, 1998;Chew et al, 1999). Second, angiotensin II is a mitogen for erythroid progenitors.…”
Section: G Erythropoiesismentioning
confidence: 99%
“…Angiotensin II modulation of erythropoietin production is hypothesized to occur via activation of AT1 receptors and/or altered renal hemodynamics (Gossmann et al, 2001;Benohr et al, 2004). However, other studies found no causative link between erythropoietin and anemia induced with ACE inhibitors or AT1 receptor antagonists (Perazella et al, 1995;Charytan et al, 1998;Chew et al, 1999). Second, angiotensin II is a mitogen for erythroid progenitors.…”
Section: G Erythropoiesismentioning
confidence: 99%
“…In our study there was no significant difference between pre and post hospitalization intact parathyroid hormone levels. Angiotensin converting enzyme (ACE) has been linked to the Epo resistance in the previous studies [28] but in more recent studies there was no difference in Epo requirements in hemodialysis patients administered ACE inhibitors versus those administered other antihypertensive medications [29,30]. We did not look at the impact of various antihypertensive agents on the Epo requirements.…”
Section: Discussionmentioning
confidence: 98%
“…Some groups suggest that ACE inhibitors reduce erythropoietin levels or induce resistance to erythropoietin (6,22,23,26). Other studies find no causative link between erythropoietin and the anemia induced by ACE inhibitors or AT 1 receptor antagonists (3,24,27,28). ACE.2 knockout mice are an excellent model system for studying the role of the renin-angiotensin system in erythropoiesis (9).…”
Section: Figurementioning
confidence: 99%